THE CONNECTION OF THE SATISFACTION OF PATIENTS FOR THE OLD AND NEW DENTURES - Neada Hysenaj; Herta Beck (European Scientific Journal, ESJ, 2014)
Introduction. One of the ultimate goals of prosthetic treatment is the achievement of the patient‘s satisfaction; defined as “patient‘s’ cognitively based evaluation of, and affectively based response to the important aspects of the structure, process and result of their service.The purpose of this study was to investigate the relation between patient’s satisfaction with their old and new removable total dentures. This study aims to help the doctor to determine a diagnose of the new dentures based on the old denture‘s satisfaction of the patient.Methods and Results 78 patients, 36 men and 42 women,aged 40-80 years old, who were volunterely chosen, were examined and treated with new dentures for a period of two years in the University Dental Clinic, Tirana and in the „Tabaku“ Dental Private Clinic. They answered a subjective questionnaire about their satisfaction from the old dentures and the new dentures 3 months after delivery. Results. Analyzing the results using the t-Test, it was found that the relation between patient‘s satisfaction from old and new denture for the following factors was statistically significant:The comfort of the denture, The factor related to the fit of the upper and lower denture, Their appereance, The ability of the patients to speek ( p< 0.05). According to the results some factors had a stronger relation of the patient‘s satisfaction with the old and new dentures according to the statistical results.The test performance shows that some factors can be used as indicators to diagnose the prognosis of the new dentures.